Uranium phosphate biomineralization by fungi. (10th March 2015) - Liang, Xinjin; Hillier, Stephen; Pendlowski, Helen; Gray, Nia; Ceci, Andrea; Gadd, Geoffrey Michael
Summary Geoactive soil fungi were investigated for phosphatase‐mediated uranium precipitation during growth on an organic phosphorus source. Aspergillus niger and Paecilomyces javanicus were grown on modified Czapek–Dox medium amended with glycerol 2‐phosphate (G2P) as sole P source and uranium nitrate. Both organisms showed reduced growth on uranium‐containing media but were able to extensively precipitate uranium and phosphorus‐containing minerals on hyphal surfaces, and these were identified by X‐ray powder diffraction as uranyl phosphate species, including potassium uranyl phosphate hydrate (KPUO6.3H2O), meta‐ankoleite [(K1.7Ba0.2)(UO2)2(PO4)2.6H2O], uranyl phosphate hydrate [(UO2)3(PO4)2.4H2O], meta‐ankoleite (K(UO2)(PO4).3H2O), uramphite (NH4UO2PO4.3H2O) and chernikovite [(H3O)2(UO2)2(PO4)2.6H2O]. Some minerals with a morphology similar to bacterial hydrogen uranyl phosphate were detected on A. niger biomass. Geochemical modelling confirmed the complexity of uranium speciation, and the presence of meta‐ankoleite, uramphite and uranyl phosphate hydrate between pH 3 and 8 closely matched the experimental data, with potassium as the dominant cation. We have therefore demonstrated that fungi can precipitate U‐containing phosphate biominerals when grown with an organic source of P, with the hyphal matrix serving to localize the resultant uranium minerals. The findings throw further light on potential fungal roles in U and P biogeochemistry as well as the application of these mechanisms for element recovery or bioremediation.